Chemical characterization of C 31 sterols from sponges and Neoproterozoic fossil sterane counterparts - Lubna Shawar; Gordon D. Love; Benjamin T. Uveges; J. Alex Zumberge; Paco Cárdenas; José-Luis Giner; Roger E. Summons (Proceedings of the National Academy of Sciences, 2025)
Putative metazoan body fossils from the Precambrian are curiously lacking morphological characteristics that link them unambiguously to extant animal phyla, including sponges. Chemical fossils such as the rare C 30 hydrocarbons 24- iso -propylcholestane (24- i pc) and 26-methylstigmastane (26-mes), however, have been proposed as evidence for the Neoproterozoic emergence of the Demospongiae (Porifera) due to their prevalence in rocks of this age and the occurrence of their sterol precursors in contemporary demosponges. However, there are alternative hypotheses which posit that diagenetic alteration products of algal sterols, or those from Rhizaria or other protists, account for the enigmatic steroid distributions observed in these ancient sedimentary rocks. Here, we report additional support for the Neoproterozoic rise of demosponges through the chemical characterization of two previously unrecognized C 31 hydrocarbons—24- n -butylcholestane (24- n bc) and 24- sec -butylcholestane (24- sec bc). Precursor C 31 sterols from contemporary demosponges, as well as a suite of synthesized C 31 sterol standards were reduced to their sterane counterparts. Gas chromatography-tandem mass spectrometry analysis and collisionally activated dissociation mass spectra confirmed the presence of 24- n bc and 24- sec bc in well-preserved early Ediacaran rocks, and the coelution of these compounds with synthetic standards enhances the robustness of these findings. Co-occurrence of abundant 24- i pc and 24- sec bc was found for numerous Neoproterozoic-Cambrian rock/oil samples, closely mimicking the abundance patterns and high structural selectivity of major C 30 and C 31 sterols detected in numerous species of modern demosponges. These findings support the hypothesized first emergence of sponges during the Neoproterozoic Era.